Gracilariopsis heteroclada concentrate as soybean meal replacement in the diet of black tiger shrimp (Penaeus monodon) postlarvae - Saromines, Carl John Matas (University of the Philippines Visayas, 2019)
This study evaluated the nutritional potential of Gracilariopsis heteroclada protein concentrate (GHPC) as an alternative protein source to soybean meal in formulated diets for the black tiger shrimp, Penaeus monodon. Five isonitrogenous andisolipidic diets were formulated replacing soybean meal protein at 0% (control), 12.5%, 25%, 50% and 75%. Each experimental diet was fed to four replicate groups of P. monodon postlarvae (PL 20, ABW, 6.13 + 0.0004 mg) for 60 days. Results showed that the growth performance of the postlarvae in terms of percent weight gain, specific growth rate, protein efficiency ratio, feed intake, feed conversion efficiency, survival, nutrient retention and biochemical composition had no significance difference (p>0.05) with the control when fed with 12.5%, 25% and 50% GHPC diets. This is possibly attributed to the high digestibility of GHPC (91.84 + 0.060%) and its good-quality protein (essential amino acid index, 0.996). However, shrimps fed with replacement levels beyond 50% exhibited significant growth depression that might be due to the presence of antinutritional compounds as observed with the reduction of digestive enzyme activities and histomorphomological changes (B-cell enlargement). Collectively, the findings suggest that GHPC could replace 50% of soybean meal protein in the diet of P. monodon. Inclusion of G. heteroclada protein concentrate is a practical approach for P. monodon aquaculture since it is a sustainable feed protein source.